The Effect of Critical Reading Strategy on Students’ Reading Ability in Comprehending Expository Text - Fitriyanti Agil Handayani; Feny Martina; Syamsul Rizal (Jadila: Journal of Development and Innovation in Language and Literature Education, 2021)
This research is aimed at finding out the effect of critical reading strategy on student's reading ability in comprehending expository text of the second grade students of MAN 1 (MODEL) Lubuklinggau in the academic year 2019/2020. This research used quantitative research with quasi experimental design. The total population of students at the second grade was 312 students of MAN 1 (MODEL) Lubuklinggau in the academic year 2019/2020. The research chose two classes as the samples of the research. The sample was selected by using purposive sampling technique. The second grade students of XI MIPA 2 was experimental class who were taught using Critical Reading Strategy and the second grade students of XI MIPA 1 was control class who were taught by the teacher. The data were collected by using test. The data were analyzed by using T-test formula. The mean score in experimental class was 79.90 while the mean score of control class was 72.31. The mean different between them was 7.59. The result of t-test showed that the value of t-count (3.970) was higher than t-table (2.024) in df 38 (0.05). Therefore, the alternative Hypothesis (Ha) was accepted while the null hypothesis (Ho) was rejected. Based on the result above, the research finding was Critical Reading Strategy was effective on students’ reading ability in comprehending expository text for the second grade students of MAN 1 (MODEL) Lubuklinggau in academic year of 2019/2020.